2020
DOI: 10.1021/acs.chemrev.9b00808
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized Extracellular Matrix-based Bioinks for Engineering Tissue- and Organ-specific Microenvironments

Abstract: Biomaterials-based biofabrication methods have gained much attention in recent years. Among them, 3D cell printing is a pioneering technology to facilitate the recapitulation of unique features of complex human tissues and organs with high process flexibility and versatility. Bioinks, combinations of printable hydrogel and cells, can be utilized to create 3D cell-printed constructs. The bioactive cues of bioinks directly trigger cells to induce tissue morphogenesis. Among the various printable hydrogels, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
305
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 326 publications
(306 citation statements)
references
References 396 publications
1
305
0
Order By: Relevance
“…Owing to these features, tubular structures were successfully printed and stably preserved in 3% VdECM bioink, thereby confirming that this material could be used as a pre‐gel suspension. In addition, several studies have demonstrated that various dECM‐based bioinks can respond to physical stimuli (e.g., shear stress), such as shear thinning behavior, [ 26 ] implying their feasibility as a supporting bath. Therefore, considering the outstanding biofunctionality of dECM bioinks, our findings suggest that the materials in this category might be promising alternatives for fabricating gel‐embedded 3D bioprinted tissue/organ models.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to these features, tubular structures were successfully printed and stably preserved in 3% VdECM bioink, thereby confirming that this material could be used as a pre‐gel suspension. In addition, several studies have demonstrated that various dECM‐based bioinks can respond to physical stimuli (e.g., shear stress), such as shear thinning behavior, [ 26 ] implying their feasibility as a supporting bath. Therefore, considering the outstanding biofunctionality of dECM bioinks, our findings suggest that the materials in this category might be promising alternatives for fabricating gel‐embedded 3D bioprinted tissue/organ models.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogels for bioink are required to (1) flow under modest pressures, (2) solidify quickly, and (3) sustain adequate integrity after building up. 50 , 51 In the sol–gel transition process, fibers in solutions can be physically or chemically cross-linked by external stimuli, such as temperature, light source, or ion concentration. 52 The main strength of physical cross-linking is the absence of cytotoxic chemical agents.…”
Section: Advances In 3d Bioprintingmentioning
confidence: 99%
“…Due to the ability of 3D printing to create porous scaffolds with complex structure and the good perspective in the 3D fabrication of personalized grafts, [ 108 ] in the past few years, a large number of articles have explored this manufacturing process to produce tissue engineering grafts. [ 109,110 ] Combined with 3D printing, the use of nanostructured materials has also been employed due to its versatile functionalities: These materials improve drug solubility and stability and act as drug carriers. In addition, they can increase the surface area of materials or help in the process of cell adhesion, specifically in cell growth.…”
Section: D Printing and Nanotechnology Alliancementioning
confidence: 99%